2022
DOI: 10.3390/pr10040738
|View full text |Cite
|
Sign up to set email alerts
|

The Formation, Stabilization and Separation of Oil–Water Emulsions: A Review

Abstract: Oil–water emulsions are widely generated in industries, which may facilitate some processes (e.g., transportation of heavy oil, storage of milk, synthesis of chemicals or materials, etc.) or lead to serious upgrading or environmental issues (e.g., pipeline plugging, corrosions to equipment, water pollution, soil pollution, etc.). Herein, the sources, classification, formation, stabilization, and separation of oil–water emulsions are systematically summarized. The roles of different interfacially active materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 195 publications
0
22
0
Order By: Relevance
“…The type of homogenizer utilized, production temperature, energy intensity, and time, as well as the state of the sample in the form of oil, oil concentration, type of emulsifier/surfactant employed, and the physicochemical characteristics of the sample, all influence the droplet size and zeta potential ( Tian et al, 2022 ). The results showed that both tested surfactants (Tween 20 or Tween 80) can form a stable nanoemulsion under experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The type of homogenizer utilized, production temperature, energy intensity, and time, as well as the state of the sample in the form of oil, oil concentration, type of emulsifier/surfactant employed, and the physicochemical characteristics of the sample, all influence the droplet size and zeta potential ( Tian et al, 2022 ). The results showed that both tested surfactants (Tween 20 or Tween 80) can form a stable nanoemulsion under experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the applicability of the secondary treatment with the aeration system was able to destabilise colloidal particles by breaking down the long chain of complex organic compounds in oil emulsion and convert them into small molecules by increasing the surface area 'colloid concentration' (Corsino et al 2018;Tian et al 2022). The outcome is in agreement with Ma et al (2020) that the contact of the microorganisms with the wastewater could be improved which allows the biosurfactant to be ready for biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of g ( r ) is a valuable tool for identifying the H-bond structure, that is, sites where potential H-bond donor and acceptor are within the hydrogen bonding distance . The hydrogen bonding interaction strength is reflected by the peak value of g ( r ) . In our methodology, several RDFs of atom pairs that can form potential H-bonds were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…26 The hydrogen bonding interaction strength is reflected by the peak value of g(r). 48 In our methodology, several RDFs of atom pairs that can form potential H-bonds were evaluated. Herein, we considered hydrogen bonding interactions of (1) aliphatic hydroxyl groups (HO9•••O7 pair), (2) aliphatic and aromatic hydroxyl groups (HO9•••O4 pair), (3) aliphatic hydroxyl groups and water (HO9•••H2O and HO7•••H2O pair), (4) aromatic hydroxyl groups and water (HO4•••H2O pair), and (5) water molecules (H2O•••H2O pair) (Figure 3).…”
Section: Estimation Of Structural and Thermophysicalmentioning
confidence: 99%